The Effects of a Baby Boom on Stock Prices and Capital Accumulation in the Presence of Social Security - Abel, Andrew B. (Econometrica, 2003)
Is the stock market boom a result of the baby boom? This paper develops an overlapping generations model in which a baby boom is modeled as a high realization of a random birth rate, and the price of capital is determined endogenously by a convex cost of adjustment. A baby boom increases national saving and investment and thus causes an increase in the price of capital. The price of capital is mean–reverting so the initial increase in the price of capital is followed by a decrease. Social Security can potentially affect national saving and investment, though in the long run, it does not affect the price of capital.